1996
DOI: 10.1111/j.1432-1033.1996.0148r.x
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Forms of Starch‐Branching Enzyme I in Solanum Tuberosum

Abstract: Western blot analysis showed the presence of three forms of starch-branching enzyme (SBE), with apparent molecular masses of 103, 97 and 80 kDa, in extracts of leaves and stored tubers of Solanum tuberosurn. The 80-kDa form was absent in extracts of fresh tuber. Active 80-kDa enzyme was partially purified from stored tubers and sequence analysis showed that it, similar to the two larger enzyme forms, was an SBE-I isoform. Limited proteolysis of isolated 103-kDa SBE-I under native conditions removed approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…Using the beb method we were able to highlight 17 and 32 sites in branches D1a and D1b, respectively (Figure 5B). The structure of the branching enzyme family and the presence of five catalytic sites included in conserved domains has been well described in Pisum sativum [31], Solanum tuberosum [32], Oryza sativa [33] and Sorghum bicolor [34]. However, none of the sites that we detected under selection matched to these catalytic domains.…”
Section: Resultsmentioning
confidence: 82%
“…Using the beb method we were able to highlight 17 and 32 sites in branches D1a and D1b, respectively (Figure 5B). The structure of the branching enzyme family and the presence of five catalytic sites included in conserved domains has been well described in Pisum sativum [31], Solanum tuberosum [32], Oryza sativa [33] and Sorghum bicolor [34]. However, none of the sites that we detected under selection matched to these catalytic domains.…”
Section: Resultsmentioning
confidence: 82%
“…This loop differs in length between SBEI and SBEII isoforms (Burton et al, 1995) and has been suggested to determine spacing between the branches (Jespersen et al, 1993). The lack of the 163-amino acid segment may not impair the ability of domain 1 to bind glucan polymers, since removal of a similar approximately 20-kD C-terminal peptide from a 103-kD potato SBEI did not alter its activity (Khoshnoodi et al, 1996). However, how the missing segments on domain 1 may affect the interactions between domain 1 and glucan polymers or starch biosynthetic enzymes cannot be predicted until further investigations have been done.…”
Section: Discussionmentioning
confidence: 99%
“…E14723), pot be I (Potato SBE I, Khoshnoodi et al 1996), pot be II (potato SBE II, Cangiano et al 1993), pea be I and be II (Burton et al1995), E.coli be (Baecker et al 1986), and Bacillus (Kiel et al 1992). Note that pea SBEI and pea SBEII sequences correspond to maize SBEII and SBEI, respectively, through differences in nomenclature conventions wSBE II-DB1.…”
Section: In Situ Hybridisationmentioning
confidence: 95%